``Cinephiles Prefer Howard Hawks'' (25th Il Cinema Ritrovato 2011) - Batistova, Anna (Iluminace, 2012)
Detailed information about Il Cinema Ritrovato 2011 in Bologna, Italy.
Keywords: film shows; lost film; film preservation